2006
DOI: 10.1111/j.1574-6968.1997.tb12571.x
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of a recombinant ureolytic Streptococcus mutans and its use to demonstrate the relationship of urease activity to pH modulating capacity

Abstract: To begin to understand the contribution of oral microbial ureolysis to the inhibition of dental caries, we sought to construct a recombinant, ureolytic mutans streptococcus and correlate the ureolytic capacity of plaque bacteria with pH moderating ability. Streptococcus mutans GS-5 was transformed with a plasmid containing the urease genes from Streptococcus salivarius 57.I. The recombinant strain, S. mutans AC04, stably maintained the urease genes. High levels of urease activity were detected, with a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…It has been suggested that plaque ureolysis can be almost entirely explained by the percentage of total detectable ureolytic bacteria in the plaque microbiota [Sissons and Cutress, 1988]. In line with this thinking, the results of a previous in vitro study showed that levels of urease activity produced by a recombinant S. mutans strain could be manipulated, resulting in small increases in urease activity, which significantly decreased environmental acidification [Clancy and Burne, 1997]. In the current study, the urease activity in plaque of caries-free individuals was higher than in saliva samples of the same individuals.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It has been suggested that plaque ureolysis can be almost entirely explained by the percentage of total detectable ureolytic bacteria in the plaque microbiota [Sissons and Cutress, 1988]. In line with this thinking, the results of a previous in vitro study showed that levels of urease activity produced by a recombinant S. mutans strain could be manipulated, resulting in small increases in urease activity, which significantly decreased environmental acidification [Clancy and Burne, 1997]. In the current study, the urease activity in plaque of caries-free individuals was higher than in saliva samples of the same individuals.…”
Section: Discussionsupporting
confidence: 68%
“…Urea is hydrolyzed by urease enzymes which are present in a number of oral bacteria. Ammonia, generated from ureolysis, can lead to considerable increase in plaque pH despite a diet rich in carbohydrates [Kleinberg, 1961;Stephen, 1993;Imfeld et al, 1995;Clancy and Burne, 1997]. Ammonia can also be produced from arginine through the arginine deiminase system (ADS), which has not been thoroughly studied as a source for alkali production.…”
mentioning
confidence: 99%
“…We observed an extremely high degree of variability in ADS activity among plaque samples, in some cases greater than 10,000-fold. In in vitro studies, a five-fold decrease in alkaligenerating potential was shown to markedly diminish the pHmoderating potential of oral bacteria (Clancy and Burne, 1997;Clancy et al, 2000). Plaque bacteria from tooth surfaces without caries lesions showed the widest range of ADS activities.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial amounts of urea are secreted continuously from saliva and gingival crevicular fluid at concentrations of 3-10 mM in healthy individuals (Epstein et al, 1980). Urea is rapidly hydrolyzed by urease from ureolytic bacteria in the oral cavity to produce two molecules of ammonia and one molecule of carbon dioxide, which could neutralize the acid end-products from carbohydrate metabolism, and may be helpful in inhibiting enamel demineralization, creating an environment less conducive to the emergence of an aciduric, acidogenic microbial communities (Clancy & Burne, 1997;Burne, 1998), and stabilizing microbial communities diversity in the face of a strong carbohydrate challenge (Shu et al, 2003). For these reasons, ureolysis is considered to be an important factor to prevent caries formation.…”
Section: Introductionmentioning
confidence: 99%